Myosin VI Haploinsufficiency Reduced Hearing Ability in Mice. (1st December 2021) - Seki, Yuta; Shitara, Hiroshi; Ishii, Rie; Ouchi, Takafumi; Yasuda, Shumpei P.; Kikkawa, Yoshiaki
Highlights: Myosin VI haploinsufficiency leads to mild hearing loss in mice. Heterozygous myosin VI knockout mice developed age-related stereocilia fusion. The outer hair cells of aged mice decreased due to myosin VI haploinsufficiency. The ribbon synapses of aged mice were decreased due to myosin VI haploinsufficiency. Abstract: In human, myosin VI (MYO6) haploinsufficiency causes postlingual progressive hearing loss. Because the usefulness of mouse models remains unclear, we produced novel Myo6 null (−/−) mutant mice and analyzed the hearing phenotypes of Myo6 +/− (+/−) heterozygous mutants. We first recorded and compared the auditory brainstem responses and distortion product otoacoustic emissions in control Myo6 +/+ (+/+) wild-type and +/− mice. These hearing phenotypes of +/− mice were mild; however, we confirmed that +/− mice developed progressive hearing loss. In particular, the hearing loss of female +/− mice progressed faster than that of male +/− mice. The stereocilia bundles of +/− mice exhibited progressive taper loss in cochlear inner hair cells (IHCs) and outer hair cells (OHCs). The loss of OHCs in +/− heterozygotes occurred at an earlier age than in +/+ mice. In particular, the OHCs at the basal area of the cochlea were decreased in +/− mice. IHC ribbon synapses from the area at the base of the cochlea were significantly reduced in +/− mice. Thus, our study indicated that MYO6 haploinsufficiency affected the detection of sounds in mice, and we suggest that +/− mice with Myo6 null alleles are useful animal models for gene therapy and drug treatment in patients with progressive hearing loss due to MYO6 haploinsufficiency.